THE COLD WAR OF 1946-1991 AND ITS CONSE - Umidovich, Aminov Bakhtiyor; Alibek , Asatov (PT. Antis International Publisher, 2024)
Looking at the world as a whole, the drift for many decades has been not towards anarchy but towards the reimposition of slavery... James Burnham's theory has been much discussed, but few people have yet considered its ideological implications—that is, the kind of world-view, the kind of beliefs, and the social structure that would probably prevail in a state which was at once unconquerable and in a permanent state of